Knowledge, attitude and practices of contraception among married women - Pegu, Bhabani; Gaur, Bhanu Pratap Singh; Sharma, Nalini; Singh, Ahanthem Santa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of current study was to assess the knowledge, attitude & practices of contraceptives among married women of reproductive age group. Methods: A cross sectional study was conducted in obstetrics & gynaecology (obs. & gynae) out door patient department (OPD), North Eastern Indira Gandhi Regional Institute of Health & Medical Sciences, Shillong, Meghalaya. 200 married women aged between 15-45 years were included in this study. Along with the socio-demographic characteristics of the women, their knowledge, attitude and practices on contraception were evaluated with the help of predesigned questionnaire. Results: It was observed that out of 200 women, majority of them were Christian (52%), illiterate (26.5%), housewife (43.5%) and belong to low socio economic status (31.5%). 174 (87%) had knowledge about contraceptive methods and it was mainly obtained from health workers (58.6%) followed by media (24.1%) and social circle (15.5%). 76 (38%)women were practicing contraceptive methods, out of which most of them were using condom (38.2%) followed by Oral Contraceptive Pills (OCPs) (27.6%), intra uterine contraceptive device (15.8%) etc. Though most of the women had knowledge about contraceptive methods majority of male 55.5% and female 51.5% were showing negative attitude towards family planning. Conclusions: The study showed, inspite of having good knowledge, utilization of contraceptives were less because of large family norm, religious myth, cultural & political barrier.